+0  
 
0
482
1
avatar

4x + 7 = 3(x–2)

Guest Feb 12, 2017
 #1
avatar+7324 
+1

4x + 7 = 3(x-2)

 

Distribute.

4x + 7 = 3x - 6

 

Subtract 3x from both sides.

1x + 7 = -6

 

Subtract 7 from both sides.

x = -13

hectictar  Feb 12, 2017

17 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.